Influence of humidity on the tribological performance of graphite reinforced aluminium anodic oxide coating - Tahir, N.A. Mat; Liza, S.; Fukuda, K.; Yaakob, Y.; Zulkifli, N.A.; Rawian, N.A.M.; Ghazazi, N.A.M. (Elsevier, 2024)
The effectiveness of graphite as self-lubricating reinforcement in anodic oxide is still unknown despite showing clear dependency towards water to provide lubrication. The objective of this study is to evaluate the tribological behavior of aluminium anodic oxide reinforced graphite coating under different relative humidity conditions. In this study, the oxide coating was reinforced with graphite varied between 0 to 20 gL−1. The graphite distribution, and structure hybridization were first analyzed. The coating with the highest sliding durability at room condition was tested under different relative humidity at 5 and 85 RH%. Overall, graphite reinforcement improved the coating's hardness and roughness. Tribological wise, coating with 1 gL−1 of graphite reinforcement has the longest durability.